The effect of giving lavender aromatherapy to pain in the first stage of labor in motherss - wiyarsih, septi; Anggrainy, Devina; Siska Ariani, Deby Utami (International Journal on Health and Medical Sciences, 2023)
As many as 810 mothers die every day from diseases/complications related to pregnancy and childbirth in 2017 and the Maternal Mortality Rate (MMR) is still high in Indonesia. In the process of childbirth there is pain that is physiological in nature but can have bad consequences if not handled properly. Labor pain can be treated in non-pharmacological ways such as aromatherapy. Objective: to determine the effect of giving lavender aromatherapy to pain in the first stage of labor in mothers. Method : pretest-posttest experiment with control group design. The experimental group was given lavender aromatherapy, the control group was not intervention. The study was conducted in to the Midwife Practice Mandiri Nini and Ria at the in June - July 2022. The sample consisted 38 Mother Maternity first Stage. Data were analyzed using paired sample t test and non-parametric Mann Whitney test. The results : the p value of each characteristic in the experimental group and the group control shows a number > 0.05. This means that the characteristics of respondents between groups are equal or homogeneous. Bivariat : the value of P 0.001 in the experimental group and 0.002 in the control group. This is that the lavender aromatherapy for the scale of labor pain. The Non-Parametric Mann Whitney Test results obtained a p value of 0.004 (p <0.05), it can be concluded that there are differences in decreasing labor pain scale in the experimental group and the control group.